2010
DOI: 10.1111/j.1439-037x.2010.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Drought Responses of Two Bambara Groundnut (Vigna subterranea L. Verdc.) Landraces Collected from a Dry and a Humid Area of Africa

Abstract: Drought adaptation strategies of two bambara groundnut landraces, Uniswa Red and S19‐3, collected from contrasting environments in Africa, were compared. Our objectives were to investigate the relative significance of effective stomatal control induced by the abscisic acid (ABA) signalling and osmotic adjustment in regulating plant water relations in general for this legume species. The ABA concentration [ABA] in the leaf increased linearly with declining relative leaf water content, and there were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 29 publications
(56 reference statements)
2
45
0
Order By: Relevance
“…a lower response to) increasing stress, which suggests some intrinsic watersaving characteristic rather than an active response to stress. A similar mechanism seems to be at play in cowpea (Hamidou et al 2007) and Bambara groundnut (Jorgensen et al 2010), where drought-resistant cultivars showed lower stomatal conductance when well watered. It would be interesting in further studies to investigate whether there is genotypic variability in this trait as well as in epicuticular wax accumulation as found in maize (Meeks et al 2012) or in the performance of the antioxidant defence system as found in wheat (Singh et al 2012) as these mechanisms could be superior in mungbean compared to common bean.…”
Section: Discussionmentioning
confidence: 86%
“…a lower response to) increasing stress, which suggests some intrinsic watersaving characteristic rather than an active response to stress. A similar mechanism seems to be at play in cowpea (Hamidou et al 2007) and Bambara groundnut (Jorgensen et al 2010), where drought-resistant cultivars showed lower stomatal conductance when well watered. It would be interesting in further studies to investigate whether there is genotypic variability in this trait as well as in epicuticular wax accumulation as found in maize (Meeks et al 2012) or in the performance of the antioxidant defence system as found in wheat (Singh et al 2012) as these mechanisms could be superior in mungbean compared to common bean.…”
Section: Discussionmentioning
confidence: 86%
“…A possible explanation to the inferior seed quality of seeds produced under rainfed conditions could be the changes in metabolic reactions including hormone signalling pathways caused by water stress, affecting reserve deposition to the developing embryo and hence compromising subsequent seed quality (Black et al 2006). Furthermore, Jørgensen et al (2010) reported that leaf abscisic acid (ABA) increased under drought conditions compared to well watered conditions implying that there was a possibility of ABA transportation to the seeds under rainfed conditions hence inhibiting germination.…”
Section: Discussionmentioning
confidence: 99%
“…They stated that drought tolerance in bambara groundnuts may be due to greater stomatal regulation, which is a drought avoidance mechanism. Recently, Jørgensen et al (2010) observed stomatal closure in two bambara groundnut landraces from two diverse locations in Africa. They also concluded that stomatal closure in 1 Pod number per plant values were rounded to the nearest integer because pod number represents discrete data 2 Statistics refer to the comparison between the 2010/11 and 2011/12 planting seasons for the three bambara groundnut landrace selections under irrigated and rain-fed conditions Table 2: Yield components of bambara groundnut landrace selections (Brown, Red and Light Brown) grown under irrigated and rain fed conditions during the 2010/11 and 2011/12 seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Collinson et al (1997) reported that drought tolerance in a Zimbabwean cream bambara groundnut landrace was the result of an ability to maintain leaf turgor pressure through a combination of osmotic adjustment, reduction in leaf area and effective stomatal control. Recently, Jørgensen et al (2010), working on two bambara groundnut landraces from diverse African origins, reaffirmed this observation. Blum (2005) classified plants that tolerate drought through enhanced soil water capture, reduced water use and maintaining cellular hydration through osmotic adjustment as drought avoidant.…”
mentioning
confidence: 82%